Modified lithium ferrite material as well as preparation method and application thereof
By generating a thin layer of nickel-ferrous oxide on the surface of lithium ferrate material and forming a carbon cladding layer, the problems of poor stability and high residual alkali content of lithium ferrate material are solved, and excellent lithium supplementation and cycling performance are achieved.
Patent Information
- Application Number
- CN202311262958.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-01
AI Technical Summary
The existing lithium ferrate materials have problems with high residual alkali or poor stability, which affects their application in lithium-ion batteries.
By doping the lithium ferrate powder with a nickel source, and mechanical grinding treatment is used to generate a thin layer of nickel-ferrous oxide on the surface of the material, combining with the formation of a vapor-phase carbon coating layer, the stability and lithium supplement performance of the material are improved.
The stability of lithium ferrate material is significantly improved, the formation of residual alkali is reduced or inhibited, and its lithium supplementation and circulation performance in lithium-ion batteries is enhanced.
Smart Images

Figure CN119742323A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion battery materials and relates to a modified lithium ferrite material and a preparation method and application thereof. Background Art
[0002] During the first charge and discharge process of lithium-ion batteries, a lithium-containing interface layer (SEI) will be generated on the surface of the negative electrode. This interface has the properties of a solid electrolyte and is crucial to the performance of lithium-ion batteries. The SEI film is insoluble in organic solvents and can exist stably in organic electrolytes. It can effectively prevent the co-embedding of solvent molecules, thereby improving the cycle performance and service life of the electrode. However, the formation of SEI consumes the active lithium in the battery, resulting in a loss of the battery's reversible capacity. At present, the first efficiency of commercial graphite negative electrodes is usually around 90%, while the first efficiency of silicon-based negative electrode materials with higher capacity is lower, usually around 85% or even lower.
[0003] In order to make up for the active lithium lost during the first charge and discharge process, the current mainstream technologies include positive electrode lithium replenishment process and negative electrode lithium replenishment process. From the perspective of technical maturity, there are many manufacturers currently engaged in the production of metal Li powder, Li foil lithium replenishment related materials and equipment, as well as lithium replenishment process research, and the industry maturity is relatively high. However, negative electrode lithium replenishment has high requirements for equipment and environment, and safety is difficult to guarantee. In contrast, the positive electrode lithium replenishment process has good safety and has no effect on existing production processes. At present, there are relatively few manufacturers and scientific research institutions engaged in the research of positive electrode lithium replenishment materials, and the preparation, modification and improvement of related lithium replenishment materials and lithium replenishment processes still need to be studied.
[0004] As a lithium-rich material, lithium ferrite has a theoretical specific capacity of 867 mAh / g and a moderate operating voltage. The inert substances generated after the first charge and discharge do not participate in the subsequent electrochemical process, making it an ideal positive electrode lithium supplement additive.
[0005] CN108878849A discloses a synthesis process of a lithium-rich oxide and a lithium-ion battery containing the lithium-rich oxide, wherein the specific synthesis process of the lithium-rich oxide is as follows: weigh a lithium source and an iron source in an appropriate molar ratio, disperse them in deionized water, and after they are completely dissolved, weigh an appropriate amount of an organic carbon source and add it to the above solution; stir the solution at 80°C until a sol is formed; spray-dry the sol to obtain a spherical precursor powder, then calcine the precursor powder in an inert gas atmosphere for a certain time, and cool it in the furnace to obtain a lithium-rich oxide Li5FeO4 / C with a core-shell structure.
[0006] CN110459748A discloses a method for preparing a carbon-coated lithium ferrite material, which comprises the following steps: (1) mixing an iron source and a lithium source, and sintering them to obtain lithium ferrite, wherein the molar ratio of the lithium source to the iron source is 5 to 25:1; (2) crushing the lithium ferrite obtained in step (1); (3) vapor-coating the crushed lithium ferrite in step (2) with a carbon source to obtain a carbon-coated lithium ferrite material.
[0007] The lithium ferrite material described in the above scheme has the problem of high residual alkali content or poor stability. Therefore, it is very necessary to develop a lithium ferrite material with low residual alkali content and good stability. Summary of the invention
[0008] The purpose of the present invention is to provide a modified lithium ferrite material and a preparation method and application thereof. The present invention can generate a unique nickel-iron-lithium oxide thin layer on the surface of the lithium ferrite material by doping lithium ferrite powder with a nickel source through mechanical grinding treatment, thereby significantly improving the stability of the lithium ferrite material, reducing or inhibiting the generation of residual alkali, and having excellent lithium replenishment performance.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a modified lithium ferrite material, comprising a nickel-doped lithium ferrite substrate and a thin iron-nickel lithium oxide layer and a carbon coating layer sequentially stacked on the surface of the nickel-doped lithium ferrite substrate, wherein the iron-nickel lithium oxide layer is in-situ generated on the surface of the nickel-doped lithium ferrite substrate. In the modified lithium ferrite material, the molar ratio of lithium element to iron element is 5:(0.9-1.1) (for example: 5:0.9, 5:0.95, 5:1, 5:1.05 or 5:1.1, etc.), the molar ratio of nickel element to lithium element is (0.01-0.05):5 (for example: 0.01:5, 0.02:5, 0.03:5, 0.04:5 or 0.05:5, etc.), and the carbon coating amount is 0.5-5wt%, for example: 0.5wt%, 1wt%, 2wt%, 3wt% or 5wt%, etc.
[0011] In the modified lithium ferrite material of the present invention, a unique nickel-iron-lithium oxide thin layer is generated on the surface of the lithium ferrite material, which significantly improves the stability of the lithium ferrite material, can reduce or inhibit the generation of residual alkali, and has excellent lithium replenishment performance.
[0012] The amount of nickel added will affect the performance of the modified lithium ferrite material. The molar ratio of the nickel element in the nickel source and the lithium element in the lithium source is controlled at (0.01-0.05):5, and the modified lithium ferrite material is better. If the amount of nickel added is too small, it is difficult to react evenly during the ball milling process, and the improvement effect is limited. If the amount of nickel added is too large, the main phase lithium ferrite structure is affected and the capacity is reduced.
[0013] In the modified lithium ferrite material provided by the present invention, the carbon coating amount is controlled to be 0.5-5wt%, which can improve the electrical properties of the modified lithium ferrite material. Preferably, the carbon coating amount is 0.8-3wt%, more preferably 1-3wt%, and further more preferably 1-2.5wt%, which can obtain better electrical properties.
[0014] According to an embodiment provided by the present invention, the molar ratio of nickel element to lithium element includes but is not limited to 0.01:5, 0.02:5, 0.03:5, 0.04:5 or 0.05:5, etc.
[0015] Preferably, the nickel element is doped by grinding, more preferably by ball milling. The nickel doping process does not include high temperature sintering and pulverization operations.
[0016] Preferably, the average thickness of the carbon coating layer is 10 to 500 nm, more preferably 80 to 400 nm, and even more preferably 100 to 300 nm.
[0017] In the present invention, the average thickness of the carbon coating layer is tested by performing a powder cross-section SEM test on the modified lithium ferrite material, then selecting at least 10 points from the SEM cross-section image, calculating their thickness values, removing the maximum and minimum values, and calculating the average value to obtain the average thickness.
[0018] The coating described in the present invention is full coating, that is, the carbon material achieves 100% coating of the nickel-doped lithium ferrite matrix.
[0019] In the modified lithium ferrite material provided by the present invention, the carbon coating layer is a homogeneous carbon coating layer. The so-called homogeneity refers to the SEM test results of the modified lithium ferrite material, and at least 50% of the carbon material outside the matrix has no obvious accumulation or agglomeration phenomenon, so as to obtain better comprehensive performance.
[0020] Preferably, the carbon source forming the carbon coating layer is a gaseous carbon source, including but not limited to any one of ethylene, acetylene, methane, ethane, propylene, propane or butene, or a combination of at least two thereof. The same type of gaseous carbon sources that can achieve the same or similar effects can also be used in the present invention.
[0021] According to some embodiments provided by the present invention, the residual alkali content of the modified lithium ferrite material is <5%; according to other embodiments provided by the present invention, the residual alkali content of the modified lithium ferrite material is <4.5%; according to some embodiments provided by the present invention, the residual alkali content of the modified lithium ferrite material is <3.5%.
[0022] The residual alkali includes LiOH and Li2CO3.
[0023] In a second aspect, the present invention provides a method for preparing a modified lithium ferrite material, the preparation method comprising the following steps:
[0024] (1) mixing a lithium source and an iron source, and sintering the mixture to obtain a lithium ferrite matrix;
[0025] (2) grinding the lithium ferrite matrix and the nickel source to obtain a nickel-doped lithium ferrite matrix;
[0026] (3) Using a carbon source, the nickel-doped lithium ferrite matrix obtained in step (2) is subjected to vapor phase carbon coating to obtain the modified lithium ferrite material.
[0027] The present invention performs a doping reaction on lithium ferrite powder and a nickel source, strictly controls the molar ratio of lithium, iron and nickel, and cooperates with appropriate process conditions to generate a unique nickel-iron-lithium oxide thin layer on the surface of the lithium ferrite material, thereby significantly improving the stability of the lithium ferrite material, reducing or inhibiting the generation of residual alkali, and having excellent lithium replenishment performance.
[0028] Preferably, the lithium source in step (1) includes any one of lithium oxide, lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrite, lithium nitrate, lithium oxalate, lithium acetate or lithium phosphate, or a combination of at least two thereof.
[0029] Preferably, the iron source includes any one of ferric chloride, ferrosoferric oxide, ferric oxide, ferric hydroxide, ferric oxyhydroxide, ferric nitrate, ferric acetate, ferric citrate, ferric phosphate, ferrous oxalate, ferric formate or ferric acetate, or a combination of at least two thereof.
[0030] Preferably, the molar ratio of the lithium element in the lithium source to the iron element in the iron source is 5:(0.9-1.1), for example: 5:0.9, 5:0.92, 5:0.95, 5:1 or 5:1.1, etc.
[0031] Preferably, the sintering process in step (1) includes one-step sintering and two-step sintering.
[0032] Preferably, the temperature of the two-step sintering is higher than the temperature of the one-step sintering.
[0033] Preferably, the one-step sintering is sintering at 100-250° C. for 0.5-4 h.
[0034] Preferably, the two-step sintering is sintering at 600-900° C. for 5-20 hours.
[0035] Preferably, the nickel source in step (2) comprises any one of nickelous oxide, nickel trioxide, nickel hydroxide, nickel hydroxide oxide, nickel nitrate, nickel nitrite, nickel carbonate, nickel oxalate or nickel acetate, or a combination of at least two thereof.
[0036] Preferably, the molar ratio of the nickel element in the nickel source to the lithium element in the lithium source is (0.01-0.05):5, for example: 0.01:5, 0.02:5, 0.03:5, 0.04:5 or 0.05:5, etc.
[0037] Preferably, the lithium ferrite matrix is crushed and sieved before the grinding treatment in step (2).
[0038] Preferably, the mesh size of the sieve is 400-500 meshes, for example, 400 mesh, 420 mesh, 450 mesh, 480 mesh or 500 mesh.
[0039] Preferably, the milling process comprises mechanochemical ball milling.
[0040] Preferably, the ball-to-material ratio of the mechanochemical ball milling is (10-45):1, for example: 10:1, 15:1, 20:1, 30:1, 40:1 or 45:1, etc.
[0041] The present invention utilizes mechanical chemical ball milling to react the nickel source with the surplus lithium on the surface of the lithium ferrite particles to generate lithium nickelate, thereby generating a thin layer of iron-nickel-lithium composite material on the surface of the lithium ferrite particles to form an excellent core-shell structure. Since lithium nickelate is more stable than lithium ferrite, it can effectively reduce the amount of residual alkali generated and improve the overall stability of the modified lithium ferrite material. Lithium nickelate itself also has a certain lithium supplementation performance.
[0042] By adopting the mechanochemical ball milling method, compared with the co-mixing sintering method, the reaction can be controlled in the surface layer of the powder, and the high-temperature sintering method is replaced, avoiding the processes of crushing and screening after sintering.
[0043] Preferably, the carbon source in step (3) comprises any one of ethylene, acetylene, methane, ethane, propylene, propane or butene, or a combination of at least two thereof.
[0044] The present invention sets the temperature of gas phase carbon coating according to the decomposition temperature of different carbon sources. The temperature of gas phase carbon coating is close to or higher than the decomposition temperature (slightly lower temperature can decompose, but the reaction is not complete), for example, 700-1000°C.
[0045] Preferably, the gas phase carbon coating in step (3) is carried out in an inert atmosphere.
[0046] Preferably, the inert atmosphere comprises nitrogen and / or argon.
[0047] The present invention sintered the carbon source gas at high temperature and deposited the carbon nano vapor on the surface of the modified lithium ferrite material, which can fully and completely coat the material, improve the stability of the material, reduce the amount of residual alkali, and improve the conductivity. Compared with ordinary carbon powder blending coating and polymer coating, the carbon nano particles have a smaller particle size and better surface modification and coating effects on the material.
[0048] Furthermore, rotating the chamber of the chemical vapor deposition furnace at a speed of 0.3 to 15.0 rpm can achieve a better coating effect, especially at 0.5 to 10.0 rpm. When the speed is too low, the modified lithium ferrite material at the bottom is not easy to contact the carbon source gas; when the speed is too high, the powder may be centrifuged and thrown up or compacted into a ball, which is not conducive to carbon coating.
[0049] Preferably, the gas phase carbon coating time is 1 to 3 hours.
[0050] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the modified lithium ferrite material as described in the second aspect.
[0051] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the third aspect.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] (1) The modified lithium ferrite material provided by the present invention can generate a unique nickel-iron-lithium oxide thin layer on the surface of the lithium ferrite material by doping lithium ferrite powder with a nickel source, controlling the molar ratio of lithium, iron and nickel, and combining appropriate process conditions, thereby significantly improving the stability of the lithium ferrite material, reducing or inhibiting the generation of residual alkali, and having excellent lithium replenishment performance.
[0054] (2) The present invention uses mechanical force to achieve the effect of chemical reaction by using mechanical force, avoids the use of high-temperature sintering, and does not need to be crushed after sintering, saving processes and energy consumption. In addition, by using mechanical force chemical ball milling, the nickel source can mainly react with the surface or the surplus lithium element in the surface layer of the lithium ferrite particles, and the generated iron-nickel-lithium composite oxide covers the surface of the lithium ferrite particles, which is beneficial to isolate the lithium ferrite from the contact with moisture and oxygen in the external environment, reduce side reactions, improve the stability of the lithium ferrite powder, have a protective effect, and are beneficial to inhibit or reduce the amount of residual alkali generated.
[0055] (3) The modified lithium ferrite material provided by the present invention uses a gaseous carbon source to form a homogeneous carbon coating layer, which has excellent conductivity and can improve electrochemical performance; in addition, this fully coated homogeneous carbon coating layer can better isolate the air and further improve environmental stability.
[0056] (4) The residual alkali content of the modified lithium ferrite of the present invention can reach less than 1.56%, the initial coulombic efficiency of the manufactured battery can reach more than 85%, the 3C discharge capacity retention rate can reach more than 88%, and the capacity retention rate after 500 cycles at 25°C can reach more than 99%. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 is a cross-sectional SEM image of the modified lithium ferrite material described in Example 1 of the present invention;
[0058] Figure 2 This is a SEM image of the modified lithium ferrite material described in Comparative Example 2. DETAILED DESCRIPTION
[0059] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0060] Example 1
[0061] This embodiment provides a modified lithium ferrite material, and the preparation method of the modified lithium ferrite material comprises the following steps:
[0062] (1) Using a mixer, 298.81 g (10 mol, equivalent to 20 mol of lithium element) of lithium oxide and 312.99 g (1.96 mol, equivalent to 3.92 mol of iron element) of ferric oxide are mixed to obtain a mixed powder. In an argon atmosphere, the mixed powder is heated to 100° C., kept at this temperature for 4.0 h, then heated to 600° C., kept at this temperature for 20.0 h, sintered at high temperature, and then naturally cooled to 25° C. to obtain lithium ferrite;
[0063] (2) In an argon atmosphere, lithium ferrite is broken up and crushed by a pulverizer, and sieved with a 500-mesh screen. The residue is crushed again, sieved again, and 2.99 g (0.04 mol, equivalent to 0.04 mol of nickel element) of nickelous oxide is added, and mixed by a mixer to obtain a mixed powder of lithium ferrite and nickelous oxide, and then the mixed powder is mechanochemically ball-milled in an argon atmosphere by a ball mill with a ball milling time of 5.0 h and a ball-to-material ratio of 30:1 to obtain a nickel-doped lithium ferrite matrix;
[0064] (3) Under an argon atmosphere, 100 g of the nickel-doped lithium ferrite substrate obtained in step (2) was placed in a chemical vapor deposition furnace, the temperature was raised to 700°C, and then acetylene was charged, the cavity of the chemical vapor deposition furnace was rotated at a speed of 0.5 rpm, and the heat was kept for 3.0 h, and then the charging of carbon source gas was stopped, and the temperature was lowered to 25°C to obtain the modified lithium ferrite material, with a carbon coating amount of 1.4 wt%.
[0065] The cross-sectional SEM image of the modified lithium ferrite material is as follows: Figure 1 As shown by Figure 1 It can be seen that a coating layer exists on the surface of a single particle of modified lithium ferrite powder prepared in the present invention, and the average thickness of the coating layer is 200 nm.
[0066] Example 2
[0067] This embodiment provides a modified lithium ferrite material, and the preparation method of the modified lithium ferrite material comprises the following steps:
[0068] (1) Using a mixer, 298.81 g (10 mol, equivalent to 20 mol of lithium element) of lithium oxide and 319.38 g (2 mol, equivalent to 4 mol of iron element) of ferric oxide were mixed to obtain a mixed powder. In an argon atmosphere, the mixed powder was heated to 250°C and kept at this temperature for 0.5 h, then heated to 900°C and kept at this temperature for 5.0 h, and after high-temperature sintering, the temperature was naturally lowered to 25°C to obtain lithium ferrite;
[0069] (2) In an argon atmosphere, lithium ferrite is broken up and crushed by a pulverizer, and sieved with a 500-mesh screen. The residue is crushed again, and 14.94 g (0.2 mol, equivalent to 0.2 mol of nickelous oxide) is added, and mixed by a mixer to obtain a mixed powder of lithium ferrite and nickelous oxide. Then, in an argon atmosphere, the mixed powder is mechanochemically ball-milled by a ball mill for 0.5 h and a ball-to-material ratio of 10:1 to obtain a nickel-doped lithium ferrite matrix;
[0070] (3) Under an argon atmosphere, 100 g of the nickel-doped lithium ferrite substrate obtained in step (2) is placed in a chemical vapor deposition furnace, the temperature is raised to 1000° C., and then ethane is filled in. The cavity of the chemical vapor deposition furnace is rotated at a speed of 10.0 rpm, and the temperature is kept constant for 1.0 h. Then, the filling of the carbon source gas is stopped, and the temperature is lowered to 25° C. to obtain the modified lithium ferrite material.
[0071] The carbon coating amount is 2.01wt%, and the average thickness of the carbon coating layer is 300nm.
[0072] Example 3
[0073] The only difference between this embodiment and embodiment 1 is that the lithium source is replaced by 20 mol lithium hydroxide, the iron source is 4.4 mol ferric chloride, and the nickel source is 0.2 mol nickel nitrate. Other conditions and parameters are exactly the same as those in embodiment 1.
[0074] The carbon coating amount is 1.4 wt %, and the average thickness of the carbon coating layer is 200 nm.
[0075] Example 4
[0076] The only difference between this embodiment and embodiment 1 is that the lithium source is replaced with 10 mol of lithium oxalate, the iron source is 3.6 mol of ferric chloride, and the nickel source is 0.2 mol of nickel hydroxide. Other conditions and parameters are exactly the same as those in embodiment 1.
[0077] The carbon coating amount is 1.4%, and the average thickness of the carbon coating layer is 200 nm.
[0078] Comparative Example 1
[0079] The only difference between this comparative example and Example 1 is that no nickel source is added, and other conditions and parameters are exactly the same as those in Example 1.
[0080] The carbon coating amount is 1.4 wt %, and the average thickness of the carbon coating layer is 200 nm.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Example 1 is that step (3) adopts a solid phase coating process, and the coating carbon source is changed to sucrose for solid phase coating. The other conditions and parameters are exactly the same as those in Example 1.
[0083] Among them, the carbon coating amount is 0.87wt%; the SEM image of the modified lithium ferrite material is as follows Figure 2 shown.
[0084] Comparative Example 3
[0085] The only difference between this comparative example and Example 1 is that the nickel source is directly mixed with the iron source and the lithium source and sintered without mechanochemical ball milling. Other conditions and parameters are exactly the same as those in Example 1.
[0086] The carbon coating amount is 1.4 wt %, and the average thickness of the carbon coating layer is 200 nm.
[0087] Comparative Example 4
[0088] The only difference between this comparative example and Example 1 is that the mass of the nickelous oxide in step (2) is 2.4 g (0.032 mol, equivalent to 0.032 mol of nickel element), and the other conditions and parameters are exactly the same as those in Example 1.
[0089] The carbon coating amount is 1.4 wt %, and the average thickness of the carbon coating layer is 200 nm.
[0090] Comparative Example 5
[0091] The only difference between this embodiment and embodiment 1 is that the mass of the nickelous oxide in step (2) is 19.74 g (0.24 mol, equivalent to 0.24 mol of nickel element), and the other conditions and parameters are exactly the same as those in embodiment 1.
[0092] The carbon coating amount is 1.4 wt %, and the average thickness of the carbon coating layer is 200 nm.
[0093] Performance Test:
[0094] 0.3 g of lithium ferrite sample prepared in the embodiment and the comparative example was added to 100 mL of methanol solvent respectively, and stirred at 800 rpm for 5 min using a 3 cm magnetic stirrer. The filtrate was filtered and the total value of residual alkali LiOH and Li2CO3 was obtained using a Mettler GS20 automatic titrator.
[0095] (1) LFP, the modified lithium ferrite material obtained in Examples 1-4 and Comparative Examples 1-5, the conductive agent SuperP, the carbon nanotubes, the binder polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) were mixed in a mass ratio of 94:2:1.5:0.5:2 to prepare a positive electrode slurry (solid content of 60%), and the double-sided surface density was 340 g / cm 2 Coated on the current collector aluminum foil, dried at 70°C, cold pressed at 4MPa at room temperature, trimmed, cut, and slit, and then welded to the tabs to make the positive electrode sheet;
[0096] (2) In an inert protective atmosphere, artificial graphite negative electrode material, conductive agent SuperP, adhesive PVDF and NMP are mixed in a mass ratio of 97.5:1.0:1.5 to form a negative electrode slurry (solid content of 50%), which is coated on the current collector copper foil with a thickness of 100 μm, dried at 100° C., cold pressed at 4 MPa at room temperature, and then trimmed, cut and stripped, and the tabs are welded to form a negative electrode sheet;
[0097] (3) Using a PE porous polymer film as a separator, the prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets, and wound to obtain a bare battery cell; the bare battery cell is placed in an aluminum-plastic shell package and placed under a relative vacuum pressure of -0.95×10 5 Pa, dried at 100 ° C to a moisture content of less than 100 ppm. The electrolyte is injected into the dried bare battery, wherein the electrolyte consists of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) (EC:EMC:DEC volume ratio = 1:1:1) and LiPF6 (concentration 1.0M), and is packaged, left to stand, formed (0.02C constant current charging for 2h, 0.1C constant current charging for 2h), shaped, and capacity tested (capacity division) to make a soft-pack lithium-ion battery.
[0098] 1. First Coulomb efficiency test:
[0099] The battery prepared above was formed and divided into different capacities using a battery test cabinet. The formation process was to charge at a constant current of 0.05C for 2.0h, then at a constant current of 0.15C for 2.5h, then at a constant current of 0.33C to 4.2V, and then at a constant voltage of 4.2V to a cut-off current of 0.02C; the divided capacities were discharged at 0.33C to 2.5V; the sum of the above charging capacities and the discharge capacity were recorded as the first charging capacity and the first discharge capacity, and the first charging specific capacity, the first discharge specific capacity and the first coulombic efficiency were calculated.
[0100] 2. Normal temperature cycle performance test:
[0101] At 25°C, charge the battery to 3.7V at 0.5C constant current and constant voltage, cut off current 0.02C, leave for 5 minutes, then discharge to 2.5V at 1C constant current, leave for 5 minutes. Repeat this cycle, calculate the capacity retention rate of the 500th cycle after 500 cycles of charge / discharge, and the calculation formula is as follows:
[0102] 500th cycle capacity retention rate (%)=(500th cycle discharge capacity / 1st cycle discharge capacity)×100%.
[0103] The test results are shown in Table 1:
[0104] Table 1
[0105]
[0106] As can be seen from Table 1, from Examples 1-4, the residual alkali content of the modified lithium ferrite of the present invention can reach less than 1.56%, the first coulomb efficiency of the manufactured battery can reach more than 85%, the 3C discharge capacity retention rate can reach more than 88%, and the capacity retention rate after 500 cycles at 25°C can reach more than 99%.
[0107] By comparing Example 1 and Comparative Example 1, it can be seen that the present invention, by doping lithium ferrite powder with a nickel source, controlling the molar ratio of lithium element, iron element and nickel element, and combining appropriate process conditions, can generate a unique nickel-iron lithium oxide thin layer on the surface of the lithium ferrite material, thereby significantly improving the stability of the lithium ferrite material, reducing or inhibiting the generation of residual alkali, and having excellent lithium replenishment performance.
[0108] From the comparison between Example 1 and Comparative Example 2, it can be seen that the present invention can fully and completely coat the modified lithium ferrite material by sintering the carbon source gas at high temperature and depositing carbon nanovapor on the surface of the modified lithium ferrite material, thereby improving the stability of the material, reducing the amount of residual alkali, and improving the conductivity. Figure 2 It can be seen that the solid-phase coating surface is uneven, some particles are exposed without carbon coating, and it is difficult to form a homogeneous carbon coating layer on the coated part.
[0109] By comparing Example 1 with Comparative Example 3, it can be seen that the present invention utilizes mechanochemical ball milling to react the nickel source with the excess lithium on the surface of the lithium ferrite particles to generate lithium nickelate, thereby generating a thin layer of iron-nickel-lithium composite material on the surface of the lithium ferrite particles to form an excellent core-shell structure. Since lithium nickelate is more stable than lithium ferrite, it can effectively reduce the amount of residual alkali generated and improve the overall stability of the modified lithium ferrite material. Lithium nickelate itself also has a certain lithium supplementation performance.
[0110] By comparing Example 1 and Comparative Examples 4-5, it can be seen that the amount of nickel added in the modified lithium ferrite material of the present invention will affect the performance of the modified lithium ferrite material. The molar ratio of the nickel element in the nickel source to the lithium element in the lithium source is controlled at (0.01-0.05):5, and the modified lithium ferrite material is better. If the amount of nickel added is too small, it is difficult to react evenly during the ball milling process, and the improvement effect is limited. If the amount of nickel added is too large, the main phase lithium ferrite structure is affected and the capacity is reduced.
[0111] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A modified lithium ferrite material, characterized in that: The modified lithium ferrite material comprises a nickel-doped lithium ferrite substrate and a thin iron-nickel lithium oxide layer and a carbon coating layer which are sequentially stacked on the surface of the nickel-doped lithium ferrite substrate. The iron-nickel lithium oxide layer is in-situ generated on the surface of the nickel-doped lithium ferrite substrate. In the modified lithium ferrite material, the molar ratio of lithium element to iron element is 5:(0.9-1.1), the molar ratio of nickel element to lithium element is (0.01-0.05):5, and the carbon coating amount is 0.5-5wt%.
2. The modified lithium ferrite material according to claim 1, characterized in that: The average thickness of the carbon coating layer is 10 to 500 nm; Preferably, the carbon source for forming the carbon coating layer is a gaseous carbon source, including any one of ethylene, acetylene, methane, ethane, propylene, propane or butene, or a combination of at least two thereof.
3. The modified lithium ferrite material according to claim 1, characterized in that: The residual alkali content of the modified lithium ferrite material is less than 5%.
4. A method for preparing a modified lithium ferrite material, characterized in that: The preparation method comprises the following steps: (1) mixing a lithium source and an iron source, and sintering the mixture to obtain a lithium ferrite matrix; (2) grinding the lithium ferrite matrix and the nickel source to obtain a nickel-doped lithium ferrite matrix; (3) Using a carbon source, the nickel-doped lithium ferrite matrix obtained in step (2) is subjected to vapor phase carbon coating to obtain the modified lithium ferrite material.
5. The preparation method according to claim 4, characterized in that: The lithium source in step (1) comprises any one of lithium oxide, lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrite, lithium nitrate, lithium oxalate, lithium acetate or lithium phosphate, or a combination of at least two thereof; Preferably, the iron source comprises any one of ferric chloride, ferroferric oxide, ferric oxide, ferric hydroxide, ferric oxyhydroxide, ferric nitrate, ferric acetate, ferric citrate, ferric phosphate, ferrous oxalate, ferric formate or ferric acetate, or a combination of at least two thereof; Preferably, the molar ratio of the lithium element in the lithium source to the iron element in the iron source is 5:(0.9-1.1). Preferably, the sintering process includes one-step sintering and two-step sintering, and the temperature of the two-step sintering is higher than the temperature of the one-step sintering.
6. The preparation method according to claim 4, characterized in that: The nickel source in step (2) comprises any one of nickelous oxide, nickel trioxide, nickel hydroxide, nickel hydroxide, nickel nitrate, nickel nitrite, nickel carbonate, nickel oxalate or nickel acetate, or a combination of at least two thereof; Preferably, the molar ratio of the nickel element in the nickel source to the lithium element in the lithium source is (0.01-0.05):
5.
7. The preparation method according to claim 4, characterized in that: Before the grinding treatment in step (2), the lithium ferrite matrix is crushed and sieved; Preferably, the milling process comprises mechanochemical ball milling; Preferably, the ball-to-material ratio of the mechanochemical ball milling is (10-45):
1.
8. The preparation method according to claim 4, characterized in that: The carbon source in step (3) includes any one of ethylene, acetylene, methane, ethane, propylene, propane or butene, or a combination of at least two thereof; Preferably, the gas phase carbon coating is performed in an inert atmosphere.
9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the modified lithium ferrite material described in claims 1-3 or the modified lithium ferrite material obtained by the method described in any one of claims 4-8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Synthesis process of lithium-rich oxide and lithium ion battery containing lithium-rich oxide
CN108878849A
Carbon-coated lithium iron oxide material and preparation method thereof
CN110459748A